1994
DOI: 10.1017/s0022112094004118
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on the Richtmyer–Meshkov instability: single-scale perturbations on a continuous interface

Abstract: We report on experiments to measure the shock-induced growth of sinusoidal perturbations on thick interfaces separating two gases of different densities. The results show that the growth rates are reduced as the interface thickness is increased. A model that accounts for the growth rate reduction caused by the presence of a finite density gradient on the interface is proposed and good agreement is obtained with the experimental results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
0
3

Year Published

1996
1996
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 21 publications
(20 reference statements)
7
62
0
3
Order By: Relevance
“…For example, in several experiments all carried out in the same shock tube, 3,19,20 Brouillette and Sturtevant reported growth linear in time after reshock by one or more reverberations between the shock tube end wall and the interface. The rate in most cases was somewhat smaller than predicted by Eq.…”
Section: ͑5͒mentioning
confidence: 99%
“…For example, in several experiments all carried out in the same shock tube, 3,19,20 Brouillette and Sturtevant reported growth linear in time after reshock by one or more reverberations between the shock tube end wall and the interface. The rate in most cases was somewhat smaller than predicted by Eq.…”
Section: ͑5͒mentioning
confidence: 99%
“…Brouillette 13 reported reasonable agreement between his model and his experiments after the interaction of the interface with the first reflected shock and expansion, even into a regime when the small amplitude approximation is no longer satisfied.…”
Section: ͑2͒mentioning
confidence: 76%
“…For an interface of finite thickness interacting with a series of incident and reflected shocks and expansions, Brouillette 13 proposed to linearly superpose the effects of each shock wave, taking for the initial condition of one shock the Atwood number, amplitude, and thickness generated by all previous interactions, so that, after Nϩ1 interactions, the amplitude is governed in time by…”
Section: ͑2͒mentioning
confidence: 99%
See 1 more Smart Citation
“…This showed that the interface amplitude decayed, with shorter wavelengths decaying exponentially quicker. Brouilette & Sturtevant (1991) accounted for diffusion effects in RMI mixing semi-analytically with an ansatz form of the classic RMI mix width growth rate, containing an additional growth rate reduction factor [9]. The growth rate reduction factor was derived to and was shown experimentally to have a δ λ scaling, again indicating that damping highly affects small wavelengths.…”
Section: Diffusionmentioning
confidence: 99%